My life with the Eskimo - Stefansson, Vilhjalmur, 1879-1962.; Anderson, Rudolph Martin, 1876-1961 (New York : Macmillan, 1951)
Includes index. Maps on lining-papers. All illustrations inserted at end. Mode of access: Internet.